Antioxidant and Biological Activities of Acacia saligna and Lawsonia inermis Natural Populations - Hosam O. Elansary; Agnieszka Szopa; Paweł Kubica; Halina Ekiert; Fahed A. Al-Mana; Mohammed A. Al-Yafrsi (Plants, 2020)
Acacia saligna and Lawsonia inermis natural populations growing in Northern Saudi Arabia might be a valuable source of polyphenols with potent biological activities. Using high-performance liquid chromatography–diode array detection (HPLC-DAD), several polyphenols were detected tentatively in considerable amounts in the methanolic leaf extracts of A. saligna and L. inermis. A. saligna mainly contained rutoside, hyperoside, quercetin 3-glucuronide, gallic acid and p-coumaric acid, whereas those of L. inermis contained apigenin 5-glucoside, apigetrin and gallic acid. Strong antioxidant activities were found in the leaf extracts of both species due to the presence of hyperoside, quercetin 3-glucuronide, gallic acid, isoquercetin, p-coumaric acid, quercitrin and rutoside. A. saligna and L. inermis leaf extracts as well as hyperoside, apigenin 5-glucoside, and quercetin 3-glucuronide significantly reduced reactive oxygen species accumulation in all investigated cancer cells compared to the control. Methanolic leaf extracts and identified polyphenols showed antiproliferative and cytotoxic activities against cancer cells, which may be attributed to necrotic cell accumulation during apoptotic periods. Antibacterial activities were also found in both species leaf extracts and were twice as high in A. saligna than L. inermis due to the high composition of rutoside and other polyphenols. Finally, strong antifungal activities were detected, which were associated with specific phenols such as rutoside, hyperoside, apigenin 5-glucoside and p-coumaric acid. This is the first study exploring the polyphenolic composition of A. saligna and L. inermis natural populations in northern Saudi Arabia and aiming at the detection of their biological activities.